2009
DOI: 10.1080/09500690802101950
|View full text |Cite
|
Sign up to set email alerts
|

How Young Children Understand Electric Circuits: Prediction, explanation and exploration

Abstract: How young children understand electric circuits 1Running head: How young children understand electric circuits RESEARCH REPORT How young children understand electric circuits: prediction, explanation and explorationHow young children understand electric circuits 2 Abstract This paper reports findings from a study of young children's views about electric circuits. Twenty-eight children aged 5 and 6 were interviewed. They were shown examples of circuits and asked to predict whether they would work and explain wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
(16 reference statements)
1
26
0
4
Order By: Relevance
“…Studies have reported that long before the onset of formal education large individual variation in engagement in the value of numbers and in early numerical skills existed among children (e.g., Aunio, Hautamäki, Sajaniemi, & Van Luit, 2009;Glauert, 2009;Glauert & Manches, 2013;National Research Council, 2009). It has also become increasingly clear that young children's early educational experiences have an impact on later outcomes (Sylvia, 2009), both in terms of educational achievement but also in the attitudes towards subjects (Glauert & Manches, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have reported that long before the onset of formal education large individual variation in engagement in the value of numbers and in early numerical skills existed among children (e.g., Aunio, Hautamäki, Sajaniemi, & Van Luit, 2009;Glauert, 2009;Glauert & Manches, 2013;National Research Council, 2009). It has also become increasingly clear that young children's early educational experiences have an impact on later outcomes (Sylvia, 2009), both in terms of educational achievement but also in the attitudes towards subjects (Glauert & Manches, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…As Fleer & Robbins, ( 2003b ) pointed out, these methods represented a signifi cant methodological development, which provided more in-depth information to science educators and teachers. Materials, especially in the case of very young children, are of crucial importance (see for example Glauert, 2009 , in whose study children were shown examples of circuits and asked to predict whether they would work and explain why, and then they were encouraged to play with the materials and make their own circuits). In other words, the materials and cards helped the researcher to elicit children's ideas, which, through questioning alone might have remained unexplored.…”
Section: The Research Methodologiesmentioning
confidence: 99%
“…Just probing children's intuitive ideas helps bring these ideas to children's attention, and this "can result in misinterpretation of their implicit understanding, as children try to make possibly incoherent ideas coherent enough to state" (Sprod, 1997 , p. 740). It has been reported that the interview procedure may have helped children to become more conscious of their own ideas and thus refl ect on their thinking in the light of further evidence (Glauert, 2009 ).…”
Section: The Research Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations